Marketing Mix Responses of Café De’ Nilo at Taguig City Amidst Pandemic - Jefferson S Marcelo; Ravenal O Dela Fuente (Research Synergy Foundation, 2023)
With this time of pandemic, the virus has an enormous effect on the businesses and things have gradually changed. This study aimed to assess the effectiveness of the marketing mix responses of Café De Nilo amid the pandemic towards increasing sales revenue by using quantitative descriptive-correlational research method. The result showed that the majority of the respondents rated Cafe De’ Nilo’s marketing mix responses effective; however, the establishment’s sales performance in 2020 was rated as poor while rated as fair in 2021. Pearson correlation also showed that the Price (p-.001), Place (p-.001), People (p-.037), Process (p-.002), and Physical Evidence (p-.003) has a significant relationship with the Cafe De Nilo’s sales performance while the promotion (p-.167) and product (p-.067) doesn’t have a significant relationship with the sales performance. This study showed the effect in terms of the sales performance and the effectiveness of marketing mix responses of Cafe De’ Nilo amidst pandemic.